Construction of a Cost-Effective Phased Array Through High-Efficiency Transmissive Programable Metasurface - Cao, Anjie; Chen, Zhansheng; Fan, Kai; You, Yuehui; He, Chong (Frontiers in Physics, 2020)
Programmable metasurfaces have shown great potential in the areas of low-complexity phase array systems in comparison with the conventional phased array antennas. In this document, a 1-bit transmissive programable metasurface with high efficiency is proposed for the cost-effective beam-steering phased array. The designed transmissive metasurface is made up of reconfigurable cells with perfect 1-bit phase tuning and less transmission losses. Through dynamically programming the 1-bit code distributions of the metasurface, real-time scanning pencil beams in desired directions can be created.